Student Health Services at Historically Black Colleges and Universities and Predominantly Black Institutions in the United States - Susan D. Mueller; Melissa A. Sutherland; M. Katherine Hutchinson; Bing Si; Yu Ding; Somatra L. Connolly (Mary Ann Liebert, 2024)
Introduction: Student health services are associated with improved health outcomes and academic success, particularly among under-resourced college populations. This study compared student health services at Historically Black Colleges and Universities (HBCUs) and Predominantly Black Institutions (PBIs) and identified factors associated with the availability of comprehensive health services (CHS). Methods: We conducted a secondary analysis of 2022 data from the Integrated Postsecondary Education Data System (IPEDS), the Minority Serving Institutions (MSIs) Directory, and the websites of HBCUs and PBIs (n=167). Bivariate and multivariate logistic regression analyses were undertaken to identify institutional variables associated with providing CHS. Institutional variables included college type (public vs. private), MSI category (HBCU vs. PBI), undergraduate enrollment, location, and proportion of Pell grant recipients. Results: Approximately 13% of HBCUs and 26% of PBIs offered no student health services; 65% of HBCUs and 39% of PBIs offered on-campus CHS with prescribing providers. Four-year HBCUs were five times more likely than 4-year PBIs to have CHS (p=0.014). Institutions with more Pell Grant recipients were less likely to offer CHS. Conclusions: Access to health care is an important social determinant of health, academic persistence, and achievement for college students. HBCUs were significantly more likely than PBIs to offer CHS. HBCUs are more likely than PBIs to have resources from federal funding, donors, and endowments that may support the development of student health centers and services. Increased funding for PBI health centers could improve access and promote health equity among the most vulnerable student populations.